Analysis of Agriculture Land Potential for Fruit Crops in Tejakula District, Buleleng Regency, Indonesia - Artanaya, I Wayan; Trigunasih, Ni Made; Mega, I Made (Universitas Panji Sakti, 2025)
Tejakula District produces fruits that are very popular with the community, but production is not yet optimal because research on land suitability has never been carried out. The aims of this research are (1) to analyze land characteristics against land suitability classes, (2) to create maps of actual and potential land suitability classes, (3) to plan land use, and (4) to provide information systems. The research used a survey and Laboratorium from March to June 2024, taking soil samples. Actual land suitability class for horticultural fruits in Tejakula District is classified as marginally suitable(S3) to not suitable(N) with limiting factors of rainfall, root condition, pH, N-total, P2O5, slope, and erosion hazard. Improvement efforts are made through soil processing, fertilizing with organic, Urea, and Phonska, improving irrigation, and making terraces. Based on the land suitability, the districts of Tejakula, as the priority, are developed to plant mango and mangosteen with quite suitable land(S2) with limiting factor temperature at Pacung, Sembiran, Bondalem, Tejakula, Tembok Village, and another Village moderately suitable(S2) with limiting factor root condition, slope. Kingfruit and Raspberryplant are quite suitable(S2) at Sembiran, Julah, Bondalem, Tejakula, Tembok village, with the limiting factor being temperature, and another Village is moderately suitable(S2) with the limiting factor being rainfall and root condition. Grape and avocado are quite suitable (S2) with the limiting factor of temperature at Pacung, Sembiran, Julah, Bondalem, Tejakula village, another village is moderately suitable(S2) with the limiting factor of root condition and slope. Land use planning by improving irrigation and applying organic fertilizer, Urea, Phonska, and making terracing.